Optimization of Behavioral Scoring for Microcredit by Utilizing E-Commerce Seller Operational Data (Seller Metrics) - Kurniawan, Hary; Febrica, Intan Astriyana; Isnaeni, Surmayanti; Rofiki, Rohman (Postgraduate, University of Mataram, 2026)
his study aims to explore the role of seller metrics on e-commerce platforms in assessing microcredit risk through a Systematic Literature Review (SLR) approach. The study reviewed recent literature from 2020 to 2025 from academic databases such as Scopus, DOAJ, and Google Scholar, using keywords like